Ground layer Cerrado plants sustain higher maximum photosynthetic rates after medium-term fire events - Scalon, Marina Corrêa; Rossatto, Davi Rodrigo [UNESP] (Elsevier, 2021)
Fire is one of the most important factors driving community assembly and ecosystem functioning in tropical savannas. However, few studies have evaluated the physiological responses of ground layer plant communities to fire disturbance. Here we used different fire regimes to investigate possible changes in leaf maximum gas exchange (Amax and gs) and leaf nutritional content (N, P, K, Ca and Mg) among different plant growth forms in savanna ground layer communities. We compared responses of ground layer plant communities under two different fire regimes: (1) no recent fire occurrence; and (2) two recurrent fire events in the last 20 years. We estimated canopy cover, soil chemical properties and species abundance on burned and unburned plots in order to calculate abundance-weighted species average trait values for gas exchange and leaf nutrient content. We found that burned plots exhibited lower canopy cover and soil organic matter content, and an overall higher soil macronutrients availability compared to unburned plots. These environmental differences clearly influenced the ground layer plant communities, which depicted higher Amax and gs in burned areas regardless of growth form. We found no significant differences among leaf nutrient traits, except for a lower Mg concentration in the burned site species. Our results support the hypothesis that distinct fire regimes select for a different set of leaf functional traits, with fire occurrence acting as an important driver increasing the maximum photosynthetic rate on the ground layer. While nutrient use seems not to be affected by medium-term recurrent fires, physiological plasticity on carbon and water use processes in response to changes in resource availability can promote the persistence of savanna species under frequent fire.
Keywords: Cerrado; Fire frequency; Herbaceous plants; Photosynthesis; Specific leaf area